2021
DOI: 10.1101/2021.01.08.21249379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection and surveillance of SARS-CoV-2 genomic variants in wastewater

Abstract: The SARS-CoV-2 lineages B.1.1.7 and 501.V2, which were first detected in the United Kingdom and South Africa, respectively, are spreading rapidly in the human population. Thus, there is an increased need for genomic and epidemiological surveillance in order to detect the strains and estimate their abundances. Here, we report a genomic analysis of SARS-CoV-2 in 48 raw wastewater samples collected from three wastewater treatment plants in Switzerland between July 9 and December 21, 2020. We find evidence for the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 44 publications
(45 reference statements)
3
104
0
2
Order By: Relevance
“…Several studies have shown that the dynamics of SARS-CoV-2 RNA in raw wastewater or sludge coincide with, or even anticipate, the dynamics of confirmed cases 7,10,11 . In addition, WBE was able to capture the introduction and spread of SARS-CoV-2 variants of concern 12 , and identify mutations that were not captured in clinical samples 13 . WBE may thus serve as a useful tool to support COVID-19 monitoring, and WBE data have already been integrated into multiple national or local COVID-19 dashboards [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the dynamics of SARS-CoV-2 RNA in raw wastewater or sludge coincide with, or even anticipate, the dynamics of confirmed cases 7,10,11 . In addition, WBE was able to capture the introduction and spread of SARS-CoV-2 variants of concern 12 , and identify mutations that were not captured in clinical samples 13 . WBE may thus serve as a useful tool to support COVID-19 monitoring, and WBE data have already been integrated into multiple national or local COVID-19 dashboards [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the most common method applied to wastewater is currently next generation sequencing (NGS), either by sequencing the viral metagenome of wastewater (Crits-Christoph et al, 2020) or by amplifying and then sequencing SARS-CoV-2 genome extracted from wastewater samples (Prado et al, 2021). While these early results are promising, many report inconsistent and/or low sequencing coverage, likely due to the low input concentrations of SARS-CoV-2 in wastewater (Fontenele et al, 2021;Jahn et al, 2021;Prado et al, 2021). Therefore, NGS-based approaches for WBE will require considerable additional optimization before they can be robustly applied to a broad variety of wastewater samples and to generate reliable high-quality data that can be used to inform public health responses.…”
Section: Introductionmentioning
confidence: 99%
“…For further analysis, we check the presence of the signature mutations of B.1.1.7; T1001I, A1708D, I2230T, SGF 3675-3677 deletion, HV 69-70 deletion, Y144 deletion, N501Y, A570D, P681H, T716I, S982A, D1118H, Q27stop, R52I, Y73C, D3L and S235F of variant B.1.1.7 59 . To verify the presence of mutations, we generate 21-bps sequences, with 10 bps before and after the mutation, and search for their presence: e.g., mutation N501Y (A23063T) corresponds to sequence CCAACCCACT T ATGGTGTTGG.…”
Section: Variant B117mentioning
confidence: 99%